2006
DOI: 10.1097/01.gim.0000237719.37908.54
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of acceptance of BRCA1 and BRCA2 test results among African American women at increased risk for hereditary breast-ovarian cancer

Abstract: Purpose: This study evaluated rates of BRCA1 and BRCA2 (BRCA1/2) test result acceptance among African American women and identified determinants of test result acceptance. Methods: Acceptance of BRCA1/2 test results was evaluated among 157 African American women at high and moderate risk for having a BRCA1/2 mutation who were offered genetic testing as part of a clinical genetic counseling research program. Results:Twenty-two percent of women received BRCA1/2 test results. Test result acceptance differed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 35 publications
2
94
1
Order By: Relevance
“…We adapted a Likert style item from our previous research (Halbert et al 2006) to measure how concerned respondents were about diseases for which FHH is a risk factor. In this study, we focused on concern about cancer and heart disease because these conditions are leading causes of morbidity and mortality nationally and among SC residents (South Carolina Department of Health and Environmental Control).…”
Section: Concern About Cancermentioning
confidence: 99%
“…We adapted a Likert style item from our previous research (Halbert et al 2006) to measure how concerned respondents were about diseases for which FHH is a risk factor. In this study, we focused on concern about cancer and heart disease because these conditions are leading causes of morbidity and mortality nationally and among SC residents (South Carolina Department of Health and Environmental Control).…”
Section: Concern About Cancermentioning
confidence: 99%
“…A number of small prevalence surveys in Black women have yielded varying results with respect to BRCA prevalence and penetrance specific to AA women Frank et al 2002;Gao et al 2000;Haffty et al 2005;John et al 2007;Kanaan et al 2003;Malone et al 2006;Mefford et al 1999;Nanda et al 2005;Olopade et al 2003;Pal et al 2004Pal et al , 2008Panguluri et al 1999;Pegoraro et al 2003;Shen et al 2000). This lack of knowledge is perpetuated by low rates of participation by AA women in clinical and research BRCA genetic counseling and testing (Armstrong et al 2005;Halbert et al 2006). Previous studies have examined the various aspects which influence the uptake of genetic counseling and testing for inherited breast cancer in Black women.…”
Section: Introductionmentioning
confidence: 99%
“…Although women with a personal history of breast cancer have a 0.56% to 1.0% risk per year of developing a second primary breast cancer, women who carry BRCA1/2 mutations have a substantially higher risk, approaching a 50% lifetime risk (6)(7)(8)(9). Breast cancer risk perceptions are important to utilization of genetic testing for BRCA1/2 mutations (10), which may be low among African American women (11). Prior research has shown that African American women without a personal history of breast cancer may not believe that they have an increased risk for developing disease, although known risk factors (e.g., family history of breast cancer in a first-degree relative) are present (12).…”
Section: Introductionmentioning
confidence: 99%